Does Balance Sheet Strength Drive the Investment Cycle? : Evidence from Pre- and Post-Crisis Cyprus - Chen, Sophia (IMF Working Papers; Working Paper, 2016)
Fixed investment was the most important contributing factor to the boom-bust cycle in Cyprus over the last decade. Investment boomed during a credit boom in mid-2000s, during which the corporate sector borrowed heavily. Investment collapsed after 2008 when the credit boom ended. Investment and corporate balance sheets further deteriorated during the Cypriot banking crisis over 2012-2014. Using firm-level investment and balance sheet data, we find that corporate indebtedness is negatively associated with investment both before and after the banking crisis, although the effect is weaker after the Cypriot banking crisis, possibly due to the reduced role of credit in driving post-crisis investment and growth. Our results suggest the need to repair corporate balance sheets to support sustainable invesetment.